Pengaruh Mobilisasi, Nutrisi dan Hygiene Luka Terhadap Penyembuhan Luka Fase Poliferasi Post Sectio Caesarea di Rumah Sakit Muhammadiyah Gresik - Handayani, Putri; Hamidah, Siti (Universitas Muhammadiyah Gresik, 2024)
Delay in mobilization risks taking a long time to recover. Good nutritionis very important for successful wound healing. The practice of personalhygiene aims to improve health where the skin is the body's first line ofdefense against infection, patient hygiene measures will increase thepatient's recovery rate. This researcher aims to determine the effect ofmobilization, nutrition and wound hygiene on wound healing in theproliferation phase of post-SC surgery at Muhammadiyah GresikHospital. Quantitative research method, population of 281 respondents,total sample of 47 respondents, non-probability sampling techniquewith purposive sampling. This research analysis uses a simple linearregression test (p<0.05). The instruments used were questionnairesheets and the Bate-Jensen assessment tool. Almost all of them haveimplemented mobilization according to the directions given by healthworkers with quite good scores (68.1%) and some are still not good(2.1%), for nutrition with quite good scores (57.4%). %) and some arestill not good (6.4%) and wound hygiene is good (66.0%) and some arestill not good (2.1%). Wound healing was 93.2%, 6.38% of woundregeneration was still continuing in treatment. From the test resultsmobilization, nutrition and wound hygiene all significant values ​​are0.000 <0.005, meaning they have an effect.There is an influence ofmobilization, nutrition and wound hygiene on post-SC proliferationphase wound healing at Muhammadiyah Gresik Hospital.